Pergeseran Identitas Arab Saudi dan Proliferasi Terorisme - Yulianti, Dina (Jurnal Review Politik, 2019)
Various reports say that Saudi Arabia is the main funder to various institutions spreading Wahhabism teachings that were considered by some as the ideological roots of radicalism and terrorism. King Salman's administration has been marked by a series of effort to establish a new identity for the moderate Saudi Kingdom. In March 2018, Crown Prince Mohammed bin Salman even admitted that his country had played a role in spreading Wahhabism, but was now determined to make changes. This article seeks to answer the question how is the real role of Saudi Arabia in the proliferation of terrorism in the world and what is the cause of the changing behaviour of Saudi Arabia's foreign policy in the era of King Salman? By using the theory of constructivism (agent-structure relations) in foreign policy, the authors argue that Saudi Arabia as an agent perceives its identity in accordance with the pressure of the global economy and the massive criticism of the international community against her support for the extreme groups. Facing these two pressures, Saudi Arabia tries to shift its identity into a moderate state. But at the same time, the identity of being a Muslim world leader vis-a-vis Iran aggravates the Saudis to continue spreading of Wahhabism. Thus it can be concluded that Saudi Arabia has dualism of identity in order to achieve polarity of its national interests.